Computational design of nanomolar-binding antibodies specific to multiple SARS-CoV-2 variants by engineering a specificity switch of antibody 80R using RosettaAntibodyDesign (RAbD) results in potential generalizable therapeutic antibodies for novel SARS-CoV-2 virus. Issue 4 (April 2023) - Hernandez, Nancy E.; Jankowski, Wojciech; Frick, Rahel; Kelow, Simon P.; Lubin, Joseph H.; Simhadri, Vijaya; Adolf-Bryfogle, Jared; Khare, Sagar D.; Dunbrack, Roland L.; Gray, Jeffrey J.; Sauna, Zuben E.
Abstract: The human infectious disease COVID-19 caused by the SARS-CoV-2 virus has become a major threat to global public health. Developing a vaccine is the preferred prophylactic response to epidemics and pandemics. However, for individuals who have contracted the disease, the rapid design of antibodies that can target the SARS-CoV-2 virus fulfils a critical need. Further, discovering antibodies that bind multiple variants of SARS-CoV-2 can aid in the development of rapid antigen tests (RATs) which are critical for the identification and isolation of individuals currently carrying COVID-19. Here we provide a proof-of-concept study for the computational design of high-affinity antibodies that bind to multiple variants of the SARS-CoV-2 spike protein using RosettaAntibodyDesign (RAbD). Well characterized antibodies that bind with high affinity to the SARS-CoV-1 (but not SARS-CoV-2) spike protein were used as templates and re-designed to bind the SARS-CoV-2 spike protein with high affinity, resulting in a specificity switch. A panel of designed antibodies were experimentally validated. One design bound to a broad range of variants of concern including the Omicron, Delta, Wuhan, and South African spike protein variants. Highlights: · Identification of well characterized antibodies that bind to SARS-CoV-1 but not to SARS-CoV-2. The use of RosettaAntibodyDesign to design variants of the anti-SARS-CoV-1 antibodies bind to SARS-CoV-2 with high affinity. Experimental validation of the antibodies designed in silico .